PENGARUH MODEL PERSONALIZED SYSTEM FOR INSTRUCTION TERHADAP HASIL TEKNIK DASAR PASSING BAWAH BOLA VOLI - Della Putri; Dicky Oktora Mudzakir; Yudhi Kharisma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the personalized system for instruction model on the learning outcomes of basic volleyball underhand passing techniques. The research method used is an experimental one. The study employed a one-group pretest-posttest design. The sample size was 28 female students, with a purposive sampling technique. Based on the hypothesis test using a paired samples t-test, the calculated t-value was 17.54 > the table t-value of 2.05, indicating significant significance. Therefore, the results of the study conclude that the personalized system for instruction model influences the learning of basic volleyball underhand passing techniques.